Prescribed versus infused enteral diet and clinical outcome in critically ill elderly - Araújo, Camila Melo de; Carvalho, Adriana Gomes Cézar de; Barbosa, Janine Maciel; Feitosa, Gina Araújo Martins; Olinto, Edcleide Oliveira dos Santos; Araújo, Pollyana Paula Almeida de; Cavalcanti, Isabel Carolina Pinto; Cavalcanti, Débora Silva; Lacerda, Aline Honor; Cabral, Caroline Sousa (Seven Editora, 2023)
The nutritional status of individuals is directly related to inadequate intake, absorption and utilization of nutrients in general. The changes resulting from aging associated with the continuous use of medications accentuate this picture. In the context of intensive care, this reality is even more challenging, since the severity of the patients' clinical condition, associated with the constant use of antibiotics and opioids, corroborate in worse tolerance to the diet offered. In view of the above, this study aimed to evaluate the association between prescribed versus  infused enteral diet and the clinical outcome of elderly patients admitted to an Intensive Care Unit. This was  a cross-sectional study conducted with elderly patients in the Intensive Care Unit of a University Hospital. Data collection was carried out using the nutritional follow-up form used in the nutritionist's daily routine and adopted by the nutrition service. The data obtained were analyzed using the statistical program SPSS version 13.0. Associations were tested using Pearson's chi-square test, where associations reaching p